Some Medicinal Aromatic Plants And Their Pharmacological Effects (Journal of Pharmaceutical Negative Results, 2023)
Aromatic plants have played a major role in vital activities such as treatment, nutrition and warming since ancient times. This process, which started with trial and error, has gone a long way with the development of technology. Aromatic plants are widely used in our country as well as all over the world. With the changing conditions, the usage areas have increased over time. Its use in medical treatments has created a more accurate and desired alternative treatment method with its knowledge. The aim of this study is a brief review about the concept of aromatic plant, its history, its place in our country and its pharmacological properties.